1956
DOI: 10.1243/pime_proc_1956_170_095_02
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Methane and Propane as Engine Fuels

Abstract: The performance of a single-cylinder, high-speed, spark-ignition engine has been studied with gaseous methane and propane as fuels. The power output and thermal efficiencies have been determined at two compression ratios, 55/1 and loll. A comparison for the same engine using liquid fuels is given in Appendix I. Both fuels will knock at high compression ratios; the limits have been determined for all ignitable mixture ratios, and also the effect of inlet temperatures has been studied. Both fuels are 'temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1966
1966
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Various engine parameters were identified such as in-cylinder pressure, brake thermal efficiency was found and compared to methane, the observations concluded that the Indicated Mean Effective Pressure (IMEP) for methane was reduced, at different loads and speeds compared to natural gas. Comparison of the performance between methane and propane characteristics was investigated by (Moore and Roy 1956). It was concluded that the maximum efficiency by utilisation of propane was greater than that of methane.…”
Section: Introductionmentioning
confidence: 99%
“…Various engine parameters were identified such as in-cylinder pressure, brake thermal efficiency was found and compared to methane, the observations concluded that the Indicated Mean Effective Pressure (IMEP) for methane was reduced, at different loads and speeds compared to natural gas. Comparison of the performance between methane and propane characteristics was investigated by (Moore and Roy 1956). It was concluded that the maximum efficiency by utilisation of propane was greater than that of methane.…”
Section: Introductionmentioning
confidence: 99%